The efficacy of some volatile oil extracts as olfactory stimuli to the fruit flies, Bactrocera zonata (Saunders) and Ceratitis capitata (Wiedemann) (Diptera : Tephritidae) - Abd El-Kareim, A. I.; Shanab, L. M.; El-Naggar, M. E.; Ghanim, N. M. A. (2009)
The experiments were carried out in guava orchard at Mansoura district, Dakahlia governorate, Egypt. Eight different plant oil extracts [olive, orange,peppermint, basil, clove (Egyptian & French), parsley and black cumin] were bioassayed as attractants for the tephritids, B. zonata and C. capitata males and females. B. zonata males and females as well as C. capitata females showed no response to all the tested oils. C. capitata males exhibited a significantly positive response to French and Egyptian clove oils; while it had no response to olive, basil, parsley and black cumin oils. The residual effectiveness of Egyptian and French clove oils were lost after nine days of exposure. Comparative study between prepared (local) and imported methyl eugenol was evaluated for 72 successive days. Statistical analysis indicated that there were significant differences between the local and imported methyl eugenol after 6, 12 and 18 days only. So, the local methyl eugenol traps may be used as a valuable tool in monitoring B. zonata. The attractiveness of B. zonata males to felt and plant fibers blocks (with different thickness) saturated with methyl eugenol was evaluated. The felt blocks captured the highest number of B. zonata males in comparison with those of plant fibers. The efficiency of plant fiber blocks was significantly affected by block thickness; while felt blocks did not affected by thickness.
Includes references.
Summary in Arabic.
1
Keywords: Fruit-flies -- Biological control; Plant extracts; Bactrocera zonata; Ceratitis capitata; attractants